Bijak Mengelola Obat: Peningkatan Kesadaran Masyarakat tentang Beyond Use Date (BUD) dan Perbedaannya dengan Expired Date (ED) sebagai Upaya Pencegahan Kesalahan Pengobatan - Mera Putri Pratitis; Aprillia Puspitasari Tunggadewi; Gunawan Firmansyah; Bagus Riyanto; Yulia Pratiwi; Putriana Ramadhani (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2026)
Drug storage is not only carried out in health facilities but can also be done independently by the community that consumes drugs, either as an emergency supply or leftover medication from previous use. Drug storage is often done without paying attention to the condition after the packaging is opened or understanding the drug's usage limit/Beyond Use Date (BUD). The community generally only looks at the expiration date/Expired Date (ED) on the drug packaging as a reference for safe drug use, and does not understand the safe usage limit for drugs after the primary packaging is opened. The purpose of this community service is to evaluate the community's knowledge and practices regarding the implementation of BUD/ED, as well as to provide education. This community service was carried out with an educational approach involving 21 people in Rejosari Village. This activity was carried out by distributing questionnaires to the community about the knowledge and practice of BUD/ED daily, then continued with the delivery of education using posters. The results of this activity indicate that the community has good knowledge of ED and BUD, but has not yet implemented ED and BUD in the storage and use of drugs independently.